The European Commission, Expert Groups, and the Policy Process Demystifying Technocratic Governance - Metz, Julia; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book challenges the assumption that policy makers' work with advisory committees is emblematic of technocratic governance. Analyzing how and why the European Commission uses expert groups in the policy process, it shows that experts not only solve technical problems, but also function as political devices and negotiators in modern governance.
Keywords: European Union; Public policy; Political science; Democracy; International organization; European Union Politics; Public Policy; Political Science; Democracy; International Organization